Extragalactic Star-forming Regions: a Study of the Physical Properties and Chemical Abundances - Muñoz Vergara, D. (2019)
Extragalactic star-forming regions are characterized by the large number of young and massive stars that ionize the surrounding gas. These regions can be observed as very luminous spots in the disk of spiral galaxies and as large areas in Blue Compact Dwarf galaxies. We present preliminary results of the study of a sample of star-forming regions in two spiral and one Blue Compact Dwarf galaxies observed with the GMOS/Long-slit configuration on the Gemini-South Telescope. We are presenting a preliminary study of two regions of each galaxy for which we estimated: reddening, electron densities, and electron temperatures by using direct method, temperature relations based on photoionization models, and empirical relations. From the electron temperatures we de- rived ionic and total chemical abundances of, O, S, N, Ne, Ar and He. In addition we computed star formation rates and the ionization state for all regions.